Relasi Antara Islam, Negara, Pluralisme, dan Pribumisasi Dalam Kacamata Gus Dur - Zulyadain Zulyadain (LPPM IAIN Sorong, 2015)
This article will truly discourse Abdurrahman Wahid’s prominent thinking or ideas like Islam and state, Pluralism, Democracy and Pribumization. These thinkings will be presented in this article. So, based on the these commands, these matters will formulate; (1) Is Neo-modernism Abdurrahman Wahid’s thinking able to said as transformation from the modernism and or traditionalism thinkings? (2) How does socialism-democracy Gus Dur’s thinking as ideology of Islam? (3) And how does Islamic Universality Gus Dur’ thinking, which views Islam as universal thinking in social life? This research finds that Abdurrahman Wahid always interprets religion as substantial. The type of Gus Dur’s thinking who has created four actual views are; Islam and state, Pluralism, Democracy, and Pribumisation of Islam.